Manifesta 1 : Biennial Exhibition in Rotterdam. - Foundation European Art Manifestation, Rotterdam; Manifesta; Bilwet; Bredikhina, Mila; Cocker, Jarvis; Eichhorn, Maria; Grünbein, Durs; Izhar, Siraj; Jaros, Piotr; Kim, Soo-Ja; Leiderman, Yuri; Mackenna, Tracy; et al. (Amsterdam : Manifesta Foundation, 1996)
Beck, Martin ; Bredikhine, Mila ; Van Caeckenbergh, Patrick ; Collishaw, Mat ; Eichhorn, Maria ; El-Hassen, Róza ; Eliasson, Olafur ; Entertainment & Co. ; Erkmen, Ayse ; Fishkin, Vadim ; Fuchs, Bernhard ; Gordon, Douglas ; Grcic, Tamara ; Grigely, Joseph ; Grönlund, Tommi ; Guilleminot, Marie-Ange ; Gutov, Dmitri ; Hanzlová, Jitka ; Hausswolff, Carl Michael von ; Hill, Christine ; Höller, Carsten ; Huang Yong Ping ; Hyber, Fabrice ; IRWIN ; Izhar, Siraj ; Jankuloski, Robert ; Jaros, Piotr ; Keser, Ivana ; Kim, Soo-Ja ; Kinoshita, Suchan ; Koo Jeong-a ; Kool, Renée ; Kopriva, Pavel ; Kulik, Oleg ; Leiderman, Yuri ; López-Cuenca, Rogelio ; Mackenna, Tracy ; Männikkö, Esko ; Marisaldi, Eva ; Marketou, Jenny ; Meintjes, Roger ; Michael, Carl ; Möller, Regina ; NestWORK ; Nisunen, Petteri ; O'Connell, Maurice ; Ondák, Roman ; Pledna, Mathias ; Plenge Jakobsen, Henrik ; Podoraga, Valery ; Pogacar, Tadej ; Post, Liza May ; Quarlana, Luca ; Rehberger, Tobias ; Rockenschaub, Gerwald ; Savadov, Arsen ; Schulz, Pit ; Senchenko, Georgy ; Solakov, Nedko ; SubREAL ; Sugar, Janos ; Taylor-Wood, Sam ; Temin, Kathy ; Tenger, Hale ; Tiravanija, Rirkrit ; Toomik, Jaan ; Trenet, Didier ; Trockel, Rosemarie ; Tronvoll, Mette ; Tzaig, Uri ; Vacas, Paco ; Valldosera, Eulàlia ; Venieri, Lydia ; Walder, Susanne ; Yass, Catherine
Engels
Manifesta 1, International Foundation Manifesta, Rotterdam, 9 June - 19 August 1996
boek
Keywords: Europa